(untitled) (Jurnal Ilmiah Sains dan Teknologi, 2021)
This study aims to provide an authentic and objective decision-making system on performance appraisal. The process of selecting outstanding lecturers should not be influenced by the element of subjectivity from those who choose, so it is felt that they do not support the process. To overcome the above problems, a decision support system was made to assist the process of selecting outstanding lecturers at the Yatna Yuana Lebak Nursing Academy. In this study, the Multiple Attribute Decision Making (MADM) problem solving using the Simple Additive Weighting (SAW) method was used. This method was chosen because it can determine the weight value of each criterion, which is then carried out a ranking process to determine the best alternative from a number of alternatives. With this ranking method, it is hoped that the assessment can be more precise because it is based on the criteria and weights that have been determined so that it gets a more accurate assessment result of who gets the predicate of outstanding lecturer. With this research, it is expected to evaluate the extent to which the system that has been implemented can affect the quality of education at the Yatna Yuana Lebak Nursing Academy.